Armed Phages: A New Weapon in the Battle Against Antimicrobial Resistance - Cleo Anastassopoulou; Deny Tsakri; Antonios-Periklis Panagiotopoulos; Chrysa Saldari; Antonia P. Sagona; Athanasios Tsakris (Viruses)
The increasing prevalence of multidrug-resistant (MDR) bacterial infections necessitates the exploration of alternative antimicrobial strategies, with phage therapy emerging as a viable option. However, the effectiveness of naturally occurring phages can be significantly limited by bacterial defense systems that include adsorption blocking, restriction–modification, CRISPR-Cas immunity, abortive infection, and NAD+ depletion defense systems. This review examines these bacterial defenses and their implications for phage therapy, while highlighting the potential of phages’ bioengineering to overcome these barriers. By leveraging synthetic biology, genetically engineered phages can be tailored to evade bacterial immunity through such modifications as receptor-binding protein engineering, anti-CRISPR gene incorporation, methylation pattern alterations, and enzymatic degradation of bacterial protective barriers. “Armed phages”, enhanced with antimicrobial peptides, CRISPR-based genome-editing tools, or immune-modulating factors, offer a novel therapeutic avenue. Clinical trials of bioengineered phages, currently SNIPR001 and LBP-EC01, showcase their potential to safely and effectively combat MDR infections. SNIPR001 has completed a Phase I clinical trial evaluating safety in healthy volunteers, while LBP-EC01 is in Phase II trials assessing its performance in the treatment of Escherichia coli-induced urinary tract infections in patients with a history of drug-resistant infections. As “armed phages” progress toward clinical application, they hold great promise for precision-targeted antimicrobial therapies and represent a critical innovation in addressing the global antibiotic resistance crisis.